EFFECT OF SEASONAL VARIATION ON TUBER BULKING RATE OF POTATO - A. A. Khan; M. S. Jilani; M. Q. Khan; M. Zubair (Journal of Animal and Plant Sciences, 2011)
Field trial was conducted to optimize the sowing date and crop growth period of potato at the Agricultural Research Institute, Dera Ismail Khan, NWFP during 2004-05. The tubers were planted on four dates with one-week interval starting from September 24 in 2004. Tubers planted at each sowing date were harvested on six different dates starting from week-10 and ending at week-15. Total number of stems increased with the delay in planting. Total numbers of tubers per unit area and percentage of large sized tubers (> 55 mm) were the highest at the earliest planting of September 24. Smaller tubers (< 35 mm) increased with delay in planting. Total tuber yield was higher at earlier planting as compared to planting at later dates. However, dry matter was higher at delayed planting. Plant dry bio-mass was higher by planting the potato earlier. Harvesting potato at various intervals also affected these parameters significantly. Total number of tubers, percent larger and medium sized tubers, tuber yield and plant dry bio-mass increased with the delay in harvesting. However, dry matter in tuber was found higher at earlier harvestings.
Keywords: Potato; Sowing dates; Harvesting dates